Modelling inhaled particle deposition in the human lung—A review - Hofmann, Werner (Journal of aerosol science, 2011)
Particle deposition in the human respiratory tract is determined by biological factors such as lung morphology and breathing patterns, and physical factors such as fluid dynamics, particle properties, and deposition mechanisms. Current particle deposition models may be grouped into two categories referring to the region of interest in the lung, i.e. either deposition in the whole lung (whole lung models), or deposition in a localized region of the lung (local scale models). In whole lung models, particle deposition in individual airways is computed by analytical equations for particle deposition efficiencies and specific flow conditions (analytical models). The present review focuses upon the philosophy of different conceptual whole lung models to determine deposition in bronchial and acinar airway generations, and to compare the deposition patterns predicted by these models. Since any modelling approach requires validation by comparison with the available experimental evidence, predicted deposition data are compared with published experimental data in human subjects. This comparison indicates that, at least during the writing of this review, deposition models can be validated only for total and, to some extent, for regional deposition. In local scale models, particle transport and deposition equations are solved by Computational Fluid and Particle Dynamics (CFPD) methods (numerical models), providing information on particle deposition patterns within selected structural elements of the lung, e.g. bronchial bifurcations. In this review, however, only their potential contribution to improve upon current analytical whole lung models will be considered. ► Review of different conceptual whole lung models. ► Comparison of deposition fractions predicted by different models. ► Comparison of theoretical predictions with experimental data.